Perancangan sistem manajemen energi pada industri manufaktur berdasarkan ISO 50001:2011 - Taufik Ridwan (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
As one manufacturing industry with a large level of energy consumption makes energy management mandatory applied at PT. XYZ, the purpose of this research is to design energy management system implementation strategy in PT. XYZ based on ISO 50001. Started by self assessment and by collecting data on the use of primary energy sources in the company, followed by processing and analyzing using simple linear regression. The self assessment results show 38% of the total value’s completeness of existing program in the clause of ISO 50001. From the processing and analyzing’s energy usage showed energy baseline and energy performance indicators (EnPI) of the company. The result of research is identifies and proposes the potential of energy savings in air compressor distribution system, steam boiler distribution, and electrical distribution system with good housekeeping, control system, and modification, proposes the energy management system implementation based on Deming’s PDCA cycle, and continued by recommending roadmap towards the implementation of energy management systems.